Three new species of reared parasitic wasps (Hymenoptera: Braconidae: Microgastrinae) from India - Gupta, Ankita (Zootaxa, 2013)
Three new species of parasitic wasps (Braconidae: Microgastrinae) from southern India are described and illustrated. Glyptapanteles clanisae sp. nov., a remarkable gregarious endoparasitoid, was bred from the caterpillar of Clanis phalaris Cramer (Lepidoptera: Sphingidae) on the host plant Pongamia pinnata (L.) (Leguminosae) along with a hyperparasitoid, Eurytoma sp. (Eurytomidae). Glyptapanteles trilochae sp. nov., was reared from parasitized caterpillar of Trilocha varians (Walker) (Lepidoptera: Bombycidae) on the host plant Ficus racemosa L. (Moraceae) along with a hyperparasitoid, Paraphylax sp. (Ichneumonidae: Cryptinae). Buluka horni sp. nov. was collected from solitary cocoons of an indeterminate caterpillar feeding on Mangifera indica L. leaves. This study also confirms a host range extension of Indian species of Glyptapanteles to Bombycidae and Sphingidae in addition to the earlier documented families viz., Papilionidae, Nymphalidae, Arctiidae, and Noctuidae.